Enhancing Capacity of Law Students on ASEAN Economic Community as Internationalization of Legal Education in Indonesia - Selfira Salsabila; Faizal Aditya Bagaskara; Chandra Dwiki Rahmawan (The Indonesian Journal of International Clinical Legal Education, 2019)
Indonesia nowadays, becomes one of the countries faced ASEANEconomic Community Era (AEC) as integrated regional economicactivities in Southeast Asia. The competitive of market, including in lawcareer area was become more challenging in AEC era. Internationalmobility activities among AEC members recognized as one of indicatorthat, Indonesia and other countries, working together in many aspects.Internationalization of law school to improve the quality of graduatesrecognized as the important thing in this era. Internationalizing of legaleducation for law school in Indonesia have to be done to face a globalcompetitive. Faculty of law or Law School as an institution that preparesstudents to be able to bring justice both theory and practice. This paperwould examine two main issues, first, is how was internationalizing oflegal education in Indonesia on facing AEC era, and second, is how thisinternationalizing can be optimized by students to develop their skillsboth theory and practice. The paper highlighted some real steps can bedone to improve the students capacity on legal learning method to faceAEC era, for the example, students are encourage to be able in Englishas international language. Faculty have to obligate and facilitatestudents to join some English training and TOEFL test preparation byfreely. Besides, Faculty also have to provide the update and sufficientbook references in law library. According to data at National Universityof Singapore (NUS) and Nanyang Technological University (NTU) ofSingapore, ratio of comparison between students and books are 1:50,meaning that 50 books provided for one student. Enhancing thestudent capacity also have to be endorsed by enforce and provokestudents to join some international competitions, and lecturers have toinvolve students on their legal projects.